Bitter greens : a novel - Forsyth, Kate, 1966- (Thomas Dunne Books/St. Martin's Press, 2014)
"After Margherita's father steals parsley from the walled garden of the courtesan Selena Leonelli, he is threatened with having both hands cut off, unless he and his wife relinquish their precious little girl. Selena is the famous red-haired muse of the artist Tiziano, first painted by him in 1512 and still inspiring him at the time of his death. She is at the center of Renaissance life in Venice, a world of beauty and danger, seduction and betrayal, love and superstition. Locked away in a tower, Margherita sings in the hope that someone will hear her. One day, a young man does"--Amazon.com.